Operando investigation of Au-MnOx thin films with improved activity for the oxygen evolution reaction. (10th March 2017) - Frydendal, Rasmus; Seitz, Linsey C.; Sokaras, Dimosthenis; Weng, Tsu-Chien; Nordlund, Dennis; Chorkendorff, Ib; Stephens, Ifan E.L.; Jaramillo, Thomas F.
Abstract: The electrochemical splitting of water holds great potential as a method for producing clean fuels by storing electricity from intermittent energy sources. The efficiency of such a process would be greatly facilitated by incorporating more active catalysts based on abundant materials for the oxygen evolution reaction. Manganese oxides are promising as catalysts for this reaction. Recent reports show that their activity can be drastically enhanced when modified with gold. Herein, we investigate highly active mixed Au-MnOx thin films for the oxygen evolution reaction, which exhibit more than five times improvement over pure MnOx . These films are characterized with operando X-ray Absorption Spectroscopy, which reveal that Mn assumes a higher oxidation state under reaction conditions when Au is present. The magnitude of the enhancement is correlated to the size of the Au domains, where larger domains are the more beneficial.